Control of a STATCOM‐assisted self‐excited induction generator‐based WECS feeding non‐linear three‐phase and single‐phase loads. Issue 4 (5th February 2019) - Satpathy, Aradhya Sambhu; Kastha, Debaprasad; Kishore, Krishna
Abstract : Self‐excited induction generator (SEIG)‐based wind energy conversion systems (WECS) are very popular for supplying stand‐alone loads at remote sites. The SEIG needs adjustable VAR to regulate its terminal voltage and frequency. Usually, a combination of a static compensator (STATCOM) and a fixed capacitor bank is used to meet this VAR demand. Here, a state feedback‐based control scheme is proposed to achieve independent control of the STATCOM DC‐link voltage and the SEIG terminal voltage. Further, to ensure harmonic‐free voltage at the SEIG terminal while supplying non‐linear three‐phase or single‐phase loads, a harmonic compensation technique is also developed. The wind turbine pitch angle control is utilised to regulate the frequency of the SEIG terminal voltage. The combined action of the proposed voltage control and pitch control strategies ensures that the load voltage and frequency are maintained at their respective rated values with very low harmonic distortion irrespective of variation in the wind speed and load demand. The performance of the proposed controllers (in terms of transient load voltage and frequency deviations and load voltage total harmonic distortion), as verified on a laboratory prototype, are found to be superior to that of similar controllers proposed in the literature.